Toward COVID-19 secure events: considerations for organizing the safe resumption of major sporting events - Ludvigsen, J. A. L.; Hayton, J. W. (Managing Sport and Leisure, 2020)
The current COVID-19 pandemic has already impacted both elite and grassroots sports in a series of ways. Whilst accepting that many answers to emerging and relevant questions cannot be provided at this stage, this commentary discusses some of the organizational prospects of "post-pandemic" sports mega-events by focusing predominantly on the topics of volunteering and security management. Importantly, these are two central facets of mega-event organization that are likely to be impacted by the current crisis in some way as the world of sports aims to resume. By considering a number of emerging questions, this commentary calls for an engagement with some of the individual and social implications related to future mega-event organizations. It sheds light on some of the potential organizational challenges and management issues related to "restarting" sports and provides some directions for future interdisciplinary work.